Interorganizational cooperation in furniture sector: a case study using the social networks analysis - Aguiar, Marísia Monte Silva (2014)
This research aims to analyze the elements involved in the development of interorganizational cooperation networks by assessing the design of Network Association of Cabinetmakers in Fortaleza (AMFOR), from his actors, properties and types. For this purpose, the procedures consist on the analytical tools of social networking through the software and Ucinet NetDraw. The results show that within six years of the Network AMFOR, their level of cooperation could enhance this collective enterprise, generating a reasonable number of regular contacts. However, it was realized the need for investment in the relationships of the actors in order to further consolidate the venture.